The The Correlation between Vocabulary Learning Strategies and Reading Comprehension - Aan Julistri; Gaya Tridinanti; Jenny Elvinna Manurung (Program Pendidikan Bahasa Inggris Universitas Tridinanti, 2024)
This study aimed to find out the correlation between vocabulary learning strategies and reading comprehension and to determine the extent to which vocabulary learning strategies contributed to the reading comprehension of students. This study used a correlational research design. The sample was selected by using a purposive sample technique, consisting of 68 students. The result of the study showed that the level of students’ vocabulary learning strategies questionnaire and reading comprehension test was in the average category. The data obtained were analyzed by using Pearson Product Moment and Regression Analysis. Pearson Product Moment was aimed to find out the correlation between vocabulary learning strategies and reading comprehension and Regression Analysis was used to determine the extent to which vocabulary learning strategies contributed to the reading comprehension of students. Based on the result of data analysis, it was revealed that there was a significant correlation between vocabulary learning strategies and reading comprehension of the eleventh-grade students of SMA Islam Az-Zahrah Palembang since the p-value (0.003) was lower than the alpha value 0.05. The r-value (0.358) was higher than the r-table (0.2012). It showed that there was a low correlation between vocabulary learning strategies and reading comprehension of the eleventh-grade students of SMA Islam Az-Zahrah Palembang. Moreover, vocabulary learning strategy contributed as much as 12.8%. It could be concluded that the contribution was in the deficient category.